2021
DOI: 10.7759/cureus.14191
|View full text |Cite
|
Sign up to set email alerts
|

Management of Heel Pad Degloving Injury After Severe Foot Crush Injury: A Case Report Study

Abstract: Crush injuries of the foot and ankle are uncommon and they have a poor prognosis leading to some form of disability. Degloving injuries of the heel and foot after crush injuries are rare and very challenging to manage due to the need for reconstruction of both osseous and soft tissue architecture. We present a salvage strategy for an open injury to the foot with extensive soft tissue detachment from the plantar and dorsal surface. A 30-year-old man was transferred to the Emergency Department from a neighboring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
(39 reference statements)
0
8
0
1
Order By: Relevance
“…We are aware of only few reports of successful reattachment of the sole of the foot. These procedures require an intact tibial neurovascular bundle, as well as the connection to remaining soft tissue bridges [ 1 , 3 , 12 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are aware of only few reports of successful reattachment of the sole of the foot. These procedures require an intact tibial neurovascular bundle, as well as the connection to remaining soft tissue bridges [ 1 , 3 , 12 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the aim of tissue reconstruction, following the rule to replace like with like tissues any reconstruction of the plantar sole with alternative tissue is less than optimal [ 15 ]. Due to the lack of durability of the reconstructed tissue and the failure to provide a stable weight-bearing area, skin grafts, fasciocutaneous or muscle flaps are prone to soft tissue complications like atrophy, hyperkeratosis, instability, ulceration, resulting in chronic heel pain and a disturbed gait [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the majority of studies reported poor prognosis leading mostly to amputations particularly when there is a complete subcutaneous detachment. 9 The mechanism of injury is an important factor affecting treatment outcomes. The external forces of injury are initially concentrated on the back of the heel when a retrograde avulsion injury occurs, but as the shear stress decreases, the surrounding vascular network and chambers filled with fat are less severely affected.…”
Section: Discussionmentioning
confidence: 99%
“…The heel pad contains elastic fibrous septa enclosing fat cells to accept loading stresses during gait; therefore, preservation of this specialized structure is preferred 1 . Injuries to the heel pad carry a high morbidity and poor prognosis leading to some form of disability that can affect a patient's quality of life 2 .…”
mentioning
confidence: 99%